Study of Sn2+ and In3+ ions in the deep eutectic solvent ethaline with surfactants: analysis of interactions through molecular dynamics, Quantum Theory of Atoms in molecules and electron localization function - Souza Júnior, José Osmar de (2024)
This work uses computational methods to investigate the behavior of Sn2+ and In3+ ions in the DES ethaline under different conditions. The Density Functional Theory (DFT) was applied for optimization, and the CHELPG method was used for partial charges attribution. Twelve Molecular Dynamics (MD) simulations were conducted, using the GROMACS software, in different temperatures (297 K and 343 K), ion proportions [Sn:In (1:1 and 1:4)], and in the presence and absence of different surfactants (CTAB and SDS). Additionally, Quantum Theory of Atoms in Molecules (QTAIM) properties were obtained after MD simulations. The results presented that In3+ showed stronger affinity for Cl− than Sn2+, but weaker and less stable interactions with OA (OA = oxygen of ethylene glycol), particularly at higher temperatures. Electron Density and Electron Localization Function analysis indicated that In-Cl interactions are stronger and more polarized than other interactions. The laplacian of electron density suggested an intermolecular nature for all interactions. The molecular graphs showed octahedral geometry around Sn2+ and tetrahedral or trigonal bipyramidal geometry around In3+. The surfactant addition altered these interactions slightly, with CTAB reducing the density of Cl− around In3+ and SDS interacting with In3+ at 297 K and in a Sn:In proportion of 1:1.